AEROBIC AND RESISTANCE EXERCISE IN PATIENTS WITH RESISTANT HYPERTENSION - Carvalho,Cristiane Junqueira de (2019)
ABSTRACT Introduction: Physical training is recommended by current guidelines as a preventive measure and as a tool to supplement pharmacological therapy in the treatment of hypertension and its pathological manifestations. However, there is considerable uncertainty regarding the best training prescription for blood pressure control in patients with resistant hypertension. Objective: To evaluate the effect, over twelve weeks, of an aerobic and resistance exercise program on blood pressure, anthropometric and biochemical parameters of patients with resistant hypertension. Methods: Eleven patients with resistant hypertension were randomly divided into two groups: resistance training and aerobic training. Blood pressure was recorded by 24-hour outpatient monitoring before and after 12-week training. The Student t-test was used to compare resistance and aerobic exercise groups, while the paired t and Wilcoxon tests were used to analyze pre- and post-exercise data. The level of significance was 0.05. Results: In the group that underwent aerobic training, mean systolic, diastolic and total blood pressure readings were significantly lower over the 24 hours analyzed, dropping by 14 mmHg, 7 mmHg and 10 mmHg, respectively, and in the waking period. The resistance training group showed no significant change in blood pressure, despite the significant improvement in HDL levels. Conclusion: Twelve weeks of aerobic exercises resulted in significantly lowered blood pressure in individuals with resistant hypertension, while resistance exercises were more effective in increasing HDL. Level of evidence II, Therapeutic study.